Diversification of Papaya Processing for Independence and Economic Improvement of the Lumpang Sewu Farmer - Ratna Juwita; Anindyah Sutra Karury; Amelia Mazidatul Mufida; Hanjar Ikrima Nanda; Layta Dinira (LPkM Universitas Bakrie, 2026)
Ponggok Village, Blitar Regency, is one of the papaya production centers in East Java with abundant harvests every year. Unfortunately, most papayas are only sold fresh without further processing, and even young papayas and their skins are often wasted. This problem continues to occur every year. Therefore, this community service program aims to empower the Lumpang Sewu Farmer Group through training in the production of economically valuable papaya products. The products developed include papaya floss, papaya chips, papaya candy, and eco-enzymes from papaya peels. The program was implemented through observation, preparation of tools and materials, product testing, training, and business evaluation and assistance. The results of the activities show a significant increase in the knowledge and skills of the participants, as evidenced by the pretest and posttest results and participant testimonials. All participants stated that they were 100% capable of producing the products, and 95% were interested in selling them. This program not only provides practical skills but also encourages economic independence and the sustainable utilization of local potential.